2017
DOI: 10.1016/j.jvolgeores.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Lava field evolution and emplacement dynamics of the 2014–2015 basaltic fissure eruption at Holuhraun, Iceland

Abstract: The 6-month long eruption at Holuhraun (August 2014-February 2015) in the Bárðarbunga-Veiðivötn volcanic system was the largest effusive eruption in Iceland since the 1783-1784 CE Laki eruption. The lava flow field covered~84 km 2 and has an estimated bulk (i.e., including vesicles) volume of~1.44 km 3. The eruption had an average discharge rate of~90 m 3 /s making it the longest effusive eruption in modern times to sustain such high average flux. The first phase of the eruption (August 31, 2014 to mid-October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 38 publications
3
163
0
Order By: Relevance
“…A more recent example is the 2014–2015 Holuhraun eruption of the Bardarbunga volcanic system in Iceland. Pedersen et al () discriminate between three different phases for the 6 month long eruption. The first phase lasted for 1.5 months and showed discharge rates between ∼350 to 100 m 3 /s.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent example is the 2014–2015 Holuhraun eruption of the Bardarbunga volcanic system in Iceland. Pedersen et al () discriminate between three different phases for the 6 month long eruption. The first phase lasted for 1.5 months and showed discharge rates between ∼350 to 100 m 3 /s.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the majority of sulphur was released soon after eruption (60% was lost during flow over a distance of 12 km), but lava flows were observed to continue outgassing for at least 2 to 4 h after solidification (Swanson and Fabbi, 1973). In contrast, the Holuhraun lava flow field exhibits a wide range of lava morphologies, varying from pāhoehoe to 'a'ā (Pedersen et al 2017) and, as demonstrated by this work, continued to release sulphur volatiles for several months after emplacement.…”
Section: Volatile Outgassing During and After Eruptionmentioning
confidence: 63%
“…where σ is the Stefan-Boltzmann constant (5.67051 × 10 −8 W/ m 2 /K 4 ), ε is the emissivity of the lava surface (assumed to be 0.95 for basalt; Patrick et al 2004), A flow is the final area of the cooling lava flow field (84 km 2 ; Pedersen et al 2017), and BT MIR,flow and BT MIR,bk are the average brightness temperatures of the flow surface pixels and surrounding background, respectively, calculated from selected MODIS-MIROVA cloud-free images (Fig. 6).…”
Section: Lava Flow Field Radiant Heat Fluxmentioning
confidence: 99%
“…The total eruption volume from Hekla volcano in the 20th century is larger than any other Icelandic central volcanoes and is similar in size to the 6 month Holuhraun eruption in 2014-2015 (Pedersen et al, 2017). However, rates of higher productivity have been observed over shorter time periods, for example, during the Krafla fires (Harris et al, 2000).…”
Section: Lava Volumes and Production Rate In Hekla In The 20th Centurymentioning
confidence: 80%